Electronic Health Records in Behavioral Research - Loft, John; Greene, Diana (International Journal of Population Data Science, 2018)
Medical records are a type of administrative record with rich potential for research of behavioral health and health policy. Developments in electronic health records (EHR) can increase access to data contained in medical records but also present some unusual challenges for research. This presentation summarizes recent literature describing the use of EHR in research and identifies issues for consideration in the preparation of research design and protocols for data collection and preparation. The discussion is presented in a framework for evaluation of data quality and fitness for use.